If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + n + 1 + n + 2 = 54 Reorder the terms: 1 + 2 + n + n + n = 54 Combine like terms: 1 + 2 = 3 3 + n + n + n = 54 Combine like terms: n + n = 2n 3 + 2n + n = 54 Combine like terms: 2n + n = 3n 3 + 3n = 54 Solving 3 + 3n = 54 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3n = 54 + -3 Combine like terms: 3 + -3 = 0 0 + 3n = 54 + -3 3n = 54 + -3 Combine like terms: 54 + -3 = 51 3n = 51 Divide each side by '3'. n = 17 Simplifying n = 17
| -6-2x=10-8 | | .25x+8=.62x+2 | | 15/(8n-32) | | 11x-33=8x+0 | | 2x^2-7x-70=3x | | 5p+2=4p-9 | | (-18)+q=5 | | 2t^2+5=2t^2+1 | | n+n+1+n+1=54 | | 15/8n-32 | | -5.9=k/3 | | 25m^2+2=3 | | 7-3x=5x+14 | | 10x-50=25 | | 3x-6x^2/x^3 | | x*0.65=28748 | | 100-38= | | 2x^2+31-9=0 | | a+2a+3a-b=7a-6 | | 5x-1=15x-72 | | 9(x+12)=18 | | 9=8+z | | 6k+2.3=-9.7 | | 2(2x-4)=3(x+3) | | 5x^2-22=8x | | m+9=4m+12 | | 5n-2=3n+2 | | 1125-5x=960-2x | | 15g+0=24+12g | | -80=9x+10 | | 1/(3x^(2/3)) | | 4(3)-6y=18 |